Characteristics and predictors of outcomes of critically Ill children with SARS-CoV-2 infection - the PICU experience - Maha Ashraf Kazi; Satyabrata Roychowdhury; Sanajit Ghosh; Manas Kumar Mahapatra; Subhajit Bhakta; Mithun Chandra Konar; Mihir Sarkar (Elsevier, 2022)
Objective: To describe the clinical characteristics, laboratory parameters, treatment, and predictors of an unfavorable outcome of critically ill children with SARS-CoV-2 infection. Method: This was a prospective observational study performed in a pediatric intensive care unit (PICU) of a tertiary care COVID referral hospital among critically ill children in the age group 1 month - 12 years admitted due to SARS-CoV-2 infection from June to December 2020. Demographic, clinical profile, pSOFA and PRISM III scores, laboratory parameters, treatment, and outcomes of the patients were recorded. Children who had a prolonged PICU stay (>14 days) or died were compared with those who were discharged from PICU within 14 days to assess predictors of unfavorable outcomes. Results: PICU admission rate among hospitalized SARS-CoV-2 infected children was 22.1% (92/416). Infants comprised the majority of the ICU population. Invasive mechanical ventilation and inotropic support were required for 28.3% and 37% of patients, respectively. Remdesivir, IVIg, and steroids were administered to 15.2%, 26.1%, and 54.3% of the subjects, respectively. The mortality rate was 7.6 %. MIS-C patients were older, less comorbid, and required less ventilator support but more inotrope support than acute severe COVID-19 patients. Predictors of unfavorable outcomes were age < 1 year, fever duration > 5 days, respiratory distress, shock, comorbidity, elevated CRP (> 50 mg/L), procalcitonin (> 6 ng/L), D-dimer (> 6 µg/L) and arterial lactate (> 2 mmol/L). Conclusion: Critically ill children with unfavorable outcomes were predominantly infants, comorbid, prolonged fever, respiratory distress, shock and elevated inflammatory markers, D-dimer and lactate. These factors may be useful for watchful monitoring and early intervention.